Returning to Paid Employment after Stroke: The Psychosocial Outcomes In StrokE (POISE) Cohort Study - Hackett, Maree L. (Public Library of Science, 2012)
OBJECTIVES: To determine which early modifiable factors are associated with younger stroke survivors' ability to return to paid work in a cohort study with 12-months of follow-up conducted in 20 stroke units in the Stroke Services NSW clinical network. PARTICIPANTS: Were aged >17 and <65 years, recent (within 28 days) stroke, able to speak English sufficiently to respond to study questions, and able to provide written informed consent. Participants with language or cognitive impairment were eligible to participate if their proxy provided consent and completed assessments on the participants' behalf. The main outcome measure was return to paid work during the 12 months following stroke. RESULTS: Of 441 consented participants (average age 52 years, 68% male, 83% with ischemic stroke), 218 were in paid full-time and 53 in paid part-time work immediately before their stroke, of whom 202 (75%) returned to paid part- or full-time work within 12 months. Being male, female without a prior activity restricting illness, younger, independent in activities of daily living (ADL) at 28 days after stroke, and having private health insurance was associated with return to paid work, following adjustment for other illnesses and a history of depression before stroke (C statistic 0·81). Work stress and post stroke depression showed no such independent association. CONCLUSIONS: Given that independence in ADL is the strongest predictor of return to paid work within 12 months of stroke, these data reinforce the importance of reducing stroke-related disability and increasing independence for younger stroke survivors. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry ANZCTRN 12608000459325